0635 Validation of a clinical scale for defining RBD severity in participants of the North American Prodromal Synucleinopathy (NAPS) consortium. (25th May 2022) - Lee-Iannotti, Joyce; Choudhury, Parichita; Busicescu, Andrea; Rangan, Pooja; Shprecher, David; Fantini, Maria-Livia; Ju, Yo-El; Boeve, Bradley; Postuma, Ronald
Abstract: Introduction: The objective of this study is to assess the validity of the REM Sleep Behavior Disorder (RBD) symptom severity scale (RBDSSS) and its correlation to the clinical global impression of severity (CGI-S) in a cohort of participants enrolled in the North American Prodromal Synucleinopathy (NAPS) study. RBD is a prodromal marker of α-synucleinopathies with no standardized tool for assessing severity in clinical or research practice. Development of a reliable scale is essential to understand risk of phenoconversion and to monitor response to treatments, particularly in future neuroprotective clinical trials. Methods: Participants and their bedpartners enrolled in the NAPS cohort filled out an 8-item questionnaire, developed by the International RBD Study Group, assessing frequency and severity of dreams, vocalizations, movements, and injuries associated with RBD, with higher scores indicating more severe symptoms. The CGI-S is a 7-point scale ranging from normal (1) to most severely ill (7) and was completed by a clinician based on an independent interview with the participant ± their bedpartners. Data was included when patient (RBDSSS-PT) and bedpartner (RBDSSS-BP) responses were both available. Total scores were derived by multiplying assigned point values for frequency and severity (for each question) and summing them for individual RBDSSS-PT scores (total possible=54) and RBDSSS-BP scores (total possible=38). Results: This cohort (n=212) included in this analysis was predominantly male (n=175) with a mean ± SE age of 65.16 ± 1.46 years. The median (interquartile range) for RBDSSS-PT, RBDSSS-BP and CGI-S was 11 (4-17), 8 (4-14.3) and 3 (3-4), respectively. Non-parametric Spearman's rank correlation coefficients (rs) for each variable pair are as follows: RBDSSS-PT vs. RBDSSS-BP, rs=0.575; RBDSSS-PT vs. CGI-S, rs=0.641; RBDSSS-BP vs. CGI-S, rs=0.463 (P<0.0001). Conclusion: A moderate correlation was observed between RBDSSS-PT and RBDSSS-BP suggesting good construct validity for the scale. CGI-S correlated moderately with RBDSSS-PT and weakly with RBDSSS-BP. Future, larger studies are needed to explore this as a possible universal and clinically applicable scale for designation of RBD disease burden and prognostication. Support (If Any):